OBSERVATIONS OF LOW-AMPLITUDE BRIGHTNESS OSCILLATIONS IN THE UNUSUAL ECLIPSING SYSTEM V718 PER (HMW 15, H 187) - Barsunova, O.; Grinin, V.; Arkharov, A.; Sergeev, S.; Shugarov, S. (Одеські астрономічні публікації, 2010)
The unusual young star V718 Per is known its prolonged eclipses with a period of 4.7 years. In additional we have discovered that for the last observational seasons (2008-2010) the low-amplitude oscillations are presented at the star’s light curve and their period is approximately a factor of 8 shorter that the main one. In contrast to the large-scale eclipses accompanied by the star’s reddening, the low-amplitude oscillations are neutral in character. So bimodal behavior can be the result of the division a circumstellar disk into two parts: an inner, dense region, and an outer, less dense disk, with a large cavity between them. Such structures emerge in the presence of a fairly massive perturbing body (or bodies) in the disk. In this case, density waves rotating with different angular velocities can be formed in each of these parts. Therefore, when such a system is observed nearly edge-on, two oscillation modes with different periods can be present in the extinction variations. We suggest that such a situation takes place in the case of V718 Per. In that case the perturbing body (or bodies) can be either a giant planets or a brown dwarfs, because of this star exhibits no signatures of spectroscopic binarity.